CYFRA 21-1 in patients with suspected cancer: evaluation of an optimal cutoff to assess the diagnostic efficacy and prognostic value - Garcia-Valdecasas Gayo Sonsoles (De Gruyter, 2020)
Chosen cutoff for cytokeratin 19 fragment antigen (CYFRA 21-1) as a tumor biomarker considerably influences its diagnostic and prognostic usefulness. The aim of the present study is to determine an optimal cutoff value for diagnostic validity of CYFRA 21-1 by Lumipulse® technology in patients with suspected cancer and also to determine if CYFRA 21-1 levels provide prognostic value.